1999
DOI: 10.1177/026309239901800202
|View full text |Cite
|
Sign up to set email alerts
|

Spine Disorders of Earth-Moving Machine Operators – Risk Assessment by Means of Simulated Spine Forces

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…From a survey of occupational drivers (of many types), Schwarze et al (58) concluded that, with increasing dose, it is probable that LBP is caused by exposure to WBV. Fritz (59) found the risk from exposure to WBV increases with age. Interestingly, Hinz et al (60) suggested that a person with a low vertebral strength may be more at risk to degenerative changes in the lumbar spine during repetitive exposures to moderate transient whole-body vibrations.…”
Section: Whole Body Vibration (Wbv)mentioning
confidence: 99%
“…From a survey of occupational drivers (of many types), Schwarze et al (58) concluded that, with increasing dose, it is probable that LBP is caused by exposure to WBV. Fritz (59) found the risk from exposure to WBV increases with age. Interestingly, Hinz et al (60) suggested that a person with a low vertebral strength may be more at risk to degenerative changes in the lumbar spine during repetitive exposures to moderate transient whole-body vibrations.…”
Section: Whole Body Vibration (Wbv)mentioning
confidence: 99%